Protected (Bypass) Protein and Feed Value of Hazelnut Kernel Oil Meal - Sariçiçek, B.Z. (Asian-Australasian Association of Animal Production Societies, 2000)
In situ and in vivo digestion trials were conducted to determine the degradation of dry matter (DM), crude protein (CP) and effective protein degradability (EPD), and digestibility of nutrients of Hazelnut kernel oil meal (HKOM), and effects of HKOM on nitrogen (N) balance. In the in situ study, nylon bag were suspended in the rumen of 3 Karayaka rams to estimate protected protein. Protein sources were analyzed for pepsin soluble protein (PSP) using a Pepsin Digestion Method, In the digestion trials, 4 Karayaka rams (36 mo.) were used in a 4 x 4 Latin square to evaluate the digestibility of nutrients and N retention to measure effects of diets containing HKOM, soybean meal (SBM) corn gluten meal (CGM) and urea (U). The degradability of DM and CP, and PSP content of HKOM were lower (p>0.05) than that of SBM, but higher (p<0.01) than that of CGM. EPD of HKOM was higher (p<0.01) than that of SBM or CGM. The apparent digestion coefficients of organic matter and CP for HKOM were lower than for SBM, but higher than for CGM, N retention of HKOM was higher than that of SBM and lower than that of CGM (p>0.05). In conclusion, these data may indicate that the HKOM is a high digestible feed source with a value between SBM and CGM.
Keywords: Bypass Protein; Hazelnut Kernel Oil Meal; Protein Degradation; Protein Sources